Role of plasma growth factor in the healing of chronic ulcers of the lower legs and foot due to ischaemia in diabetic patients - Miłek, Tomasz; Baranowski, Krzysztof; Zydlewski, Piotr; Ciostek, Piotr; Mlosek, Krzysztof; Olszewski, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : It has been demonstrated that plasma growth factor (PGF) responsible for proliferation of smooth muscle cells and fibroblasts significantly shortens treatment duration. Aim : To determine the role of human growth factor in the healing of ulcers due to ischaemic diabetic foot syndrome (DFS) following previous angioplasty of the blood vessels of the lower leg and foot. Material and methods : The study group included 50 patients with ischaemic diabetic foot complicated by lower leg ulcers in which angioplasty of the stenotic arteries in the distal lower leg and foot was performed. It has been assumed that the area of the ulcer cannot exceed 5 cm 2 . Following surgical debridement, each patient received platelet-rich plasma in the form of dressings applied on an ulcer, followed by hydrocolloid dressings. Each dressing was replaced after 10 days, and this procedure was repeated after 20 and 30 days of treatment. The control group included 50 patients with ischaemic diabetic foot complicated by an ulcer up to 5 cm 2 . Angioplasty of the lower leg arteries was also performed in this group. However, after surgical debridement, wounds were covered with hydrocolloid dressings. Results : After 3 months of combined treatment, all wounds in the study group healed whereas in the control group, only wounds of the smallest size healed. Conclusions : Combined treatment of ulcers due to ischaemic DFS with endovascular procedures to re-establish blood flow to the vessels and dressings with autologous platelet-rich plasma significantly shortens the healing time.